2015
DOI: 10.1016/j.fuel.2015.07.064
|View full text |Cite
|
Sign up to set email alerts
|

The potential of RCCI concept to meet EURO VI NOx limitation and ultra-low soot emissions in a heavy-duty engine over the whole engine map

Abstract: ElsevierBenajes Calvo, JV.; Pastor Soriano, JV.; García Martínez, A.;. The potential of RCCI concept to meet EURO VI NOx limitation and ultra-low soot emissions in a heavy-duty engine over the whole engine map. Fuel. 159:952-961. doi:10.1016Fuel. 159:952-961. doi:10. /j.fuel.2015.064.The potential of RCCI concept to meet EURO VI NOx limitation and ultra-low soot emissions in a heavy-duty engine over the whole engine map Fuel, Volume 159, 1 November 2015, Pages 952-961. http://dx.doi.org/10.1016/j.fuel.2015 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…In this sense, several studies confirm that, in order to achieve high efficiency while reducing NOx and soot emissions, the higher portion of the energy should come from the low reactivity fuel [22,26]. This fact suggests that the low reactivity fuel characteristics and its amount in the blend must have a key role on the in-cylinder reactivity, so this will be the fuel source varied during the investigation.…”
Section: Paths For Increasing Rcci Efficiencymentioning
confidence: 84%
“…In this sense, several studies confirm that, in order to achieve high efficiency while reducing NOx and soot emissions, the higher portion of the energy should come from the low reactivity fuel [22,26]. This fact suggests that the low reactivity fuel characteristics and its amount in the blend must have a key role on the in-cylinder reactivity, so this will be the fuel source varied during the investigation.…”
Section: Paths For Increasing Rcci Efficiencymentioning
confidence: 84%
“…include fuel ratio [14], injection strategy [15][16][17][18], EGR rate [19], compression ratio [16], bowl geometry [20,21], stability control, and utilization of two injectors.…”
Section: Improvement Trends For Internal Combustion Enginesmentioning
confidence: 99%
“…In all the cases, the most suitable combination of biofuels was B7 +E10-95 as it provided highest gross indicated efficiency with ultra-low NOx and soot low emissions. In addition, further work showed that this combination of biofuels allows achieving a clean and efficient operation up to full load when using an effective CR of 11:1, but practically the RCCI concept is limited to around 70% load due to excessive in-cylinder PRRs [26]. Taking into account this experimental background and considering the high CR of the production engine used in the current, the LRF selected for performing this study was E20-95.…”
Section: Fuels and Deliverymentioning
confidence: 99%
“…To explore the RCCI operating limits with a well-defined criteria, an experimental procedure derived from the one described in [26] was applied. This procedure is summarized in Fig.…”
Section: Experimental Procedures Considerationsmentioning
confidence: 99%
See 1 more Smart Citation